“Aún mejorando el mundo”: experiências de estudantes venezuelanos/as em escolas paraibanas - Gordillo Sánchez, Daniel Guillermo (2024)
With approximately eight million displaced people worldwide, the Venezuelan migratory phenomenon stands out as one of the most significant and unprecedented population movements in the Americas, bringing many complex challenges to host societies. Through an interdisciplinary theoretical-methodological framework that incorporates contributions from cultural studies in education, linguistic studies, and anthropology, this Thesis investigates the experiences of four young Venezuelan students who settled in Paraíba between 2018 and 2021 and enrolled in public schools in the region. This is an ethnographic study focusing on two 14-year-old siblings attending the eighth grade in João Pessoa, a 15-year-old student studying the ninth grade remotely in the same city, and a fourth participant, 16 years old, in the final year of high school in Conde (PB), a municipality in the metropolitan region of João Pessoa. The main goal of the research is to apprehend the meanings these young people attribute to their adaptation and integration process in the public schools of Paraíba, exploring the main educational obstacles and challenges they face in these institutions. Similarly, the Thesis examines the strategies that migrant students employ to overcome barriers and to get opportunities for schooling, learning, and socialization. The study highlights that the difficulties these young people faced were mainly related to learning and mastering the Portuguese language, the COVID-19 pandemic, and their invisibility in the school space. However, far from adopting a passive position in the face of adversities, it was possible to observe the resilience, investments, talents, and creativity of the young Venezuelans; these qualities not only facilitate overcoming daily challenges and barriers, both within and outside the school space but also show the way for the development of intercultural and decolonial educational policies, aiming to improve the reception of this population in the Brazilian school system.